Morphological and Histological Study of The Fore Brain (Cerebrum) In Quail Coturnix coturnix (Linnaeus, 1758) - B. Abid, Asmaa; A. Al-Bakri, Nahla (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The morphological and histological aspects of fore brain (Cerebrum) in quail (Coturnix coturnix) have been investigated, results of the present study revealed that the cerebrum in quail is large size triangular shape, its surface contains folds of shallow grooves. Microscopical examination declears that cerebrum consists of two regions, the first represents pallium which includes the external corticoid area which consist of hyperpallium and the dorsolateral corticoid area, it consists of piriform cortex and hippocampal complex. The second region is the internal corticoid areas dorsal ventricular ridge which contains the mesopallium, nidopallium and archopallium. he large size pyramidal neurons appeared in the nidopallium surrounded the crescent shaped lateral ventricles. The subpallium region consists of two regions represented by striatum which contains neuronal fibers and pallium which is appeared small and pale colour and represented the deepest part of cerebrum